2023
DOI: 10.3389/fped.2022.1006817
|View full text |Cite
|
Sign up to set email alerts
|

Low total cholesterol predicts early death in children with hemophagocytic lymphohistiocytosis

Abstract: BackgroundHemophagocytic lymphohistiocytosis (HLH) is a rapidly progressive and potentially life-threatening disorder. Identifying risk factors and timely adjustment of the given treatment regimens is critical to reducing the early mortality in HLH patients. Hypocholesterolemia has been reported to be associated with poor prognosis in a variety of critical illnesses. However, serum cholesterol is rarely studied in HLH patients, and its prognostic value is unclear.MethodsWe conducted a retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The early use of immunochemotherapy is beneficial in improving survival, with more than half of HLH patients treated with the HLH-94 regimen achieving 5-year long-term survival, timely immunochemotherapy regimens can rapidly control inflammatory factors and reduce ensuing organ damage [ 31 ]. Our research group has also previously confirmed that decreased TC and elevated BUN are independent risk factors for early death in children with HLH [ 32 ]。Lower cholesterol levels may impair the ability to regulate inflammatory immune responses and neutralize endotoxins in pathological conditions, ultimately leading to a storm of uncontrolled inflammatory factors [ 33 ]. Elevated BUN indicates that patients with HLH may have more severe circulatory perfusion deficits, infections, or acute kidney injury, which increases the risk of death [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 67%
“…The early use of immunochemotherapy is beneficial in improving survival, with more than half of HLH patients treated with the HLH-94 regimen achieving 5-year long-term survival, timely immunochemotherapy regimens can rapidly control inflammatory factors and reduce ensuing organ damage [ 31 ]. Our research group has also previously confirmed that decreased TC and elevated BUN are independent risk factors for early death in children with HLH [ 32 ]。Lower cholesterol levels may impair the ability to regulate inflammatory immune responses and neutralize endotoxins in pathological conditions, ultimately leading to a storm of uncontrolled inflammatory factors [ 33 ]. Elevated BUN indicates that patients with HLH may have more severe circulatory perfusion deficits, infections, or acute kidney injury, which increases the risk of death [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 67%